2022
DOI: 10.1155/2022/9213220
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Stalk Germ Cell Tumors: Retrospective Case Series and Literature Review

Abstract: Objective. Intracranial germ cell tumors with isolated pituitary stalk involvement are rare. Early recognition and long-term monitoring deserve further exploration. Methods. A retrospective study reviewing eleven intracranial germ cell tumor patients with isolated pituitary stalk involvement was performed. Results. Seven boys and four girls who presented with a hyperintense pituitary stalk on postcontrast T1-weighted magnetic resonance imaging without a posterior pituitary signal were included. The average max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In the present study, although the differences in neuroendocrine outcomes are not significant between subtypes 1 and 2, it could be predicted that patients with the subtype 1 and 2 images would have better neuroendocrine outcomes than those with non-sellar patients. Combined with the previous study on pituitary stalk GCT ( 16 ), this study indicated that a limited sellar iGCT located in the pituitary and the floor of the third ventricle, including solitary and bifocal lesions, has the potential to spontaneously improve neuroendocrine outcomes. Hence, it is valuable evidence to support the role of sellar lesion image in predicting neuroendocrine outcomes and in administrating individual hormone replacement treatment.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, although the differences in neuroendocrine outcomes are not significant between subtypes 1 and 2, it could be predicted that patients with the subtype 1 and 2 images would have better neuroendocrine outcomes than those with non-sellar patients. Combined with the previous study on pituitary stalk GCT ( 16 ), this study indicated that a limited sellar iGCT located in the pituitary and the floor of the third ventricle, including solitary and bifocal lesions, has the potential to spontaneously improve neuroendocrine outcomes. Hence, it is valuable evidence to support the role of sellar lesion image in predicting neuroendocrine outcomes and in administrating individual hormone replacement treatment.…”
Section: Discussionsupporting
confidence: 64%
“…Scarce data is available to compare sex-speci c differences in patients with GCT and PST. Chen et al published a case series of patients with GCT with isolated pituitary stalk involvement and described eleven patients in a period of six years (2015-2021) with no signi cant differences in sex [5]. However, GCT are described more frequently in males than females, with a ratio of about 4 to 1 [10].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent clinical manifestations are anterior pituitary dysfunction, AVD, visual eld de cits and signs of elevated intracranial pressure. Regarding pituitary dysfunction, the most common clinical presentation is polyuria and polydipsia [5]. AVD is very common and other anterior pituitary hormone de cits occur in half of the patients [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…The pituitary stalk connects the median eminence of the hypothalamus to the pituitary gland [1]. Pathologies involving the pituitary stalk may present with hormonal deficiencies, precocity and non-specific symptoms such as headache and visual disturbance [2][3][4][5][6]. Isolated pituitary stalk thickening (PST) may be a result of neoplasms, such as germ cell tumors (GCTs) and Langerhans cell histiocytosis (LCH), inflammation, infection or congenital variants or can be idiopathic [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%